Laser-Facilitated Additive Manufacturing Enables Fabrication of Biocompatible Neural Devices - Ailke Behrens; Jan Stieghorst; Theodor Doll; Ulrich P. Froriep (Sensors, 2020)
Current personalized treatment of neurological diseases is limited by availability of appropriate manufacturing methods suitable for long term sensors for neural electrical activities in the brain. An additive manufacturing process for polymer-based biocompatible neural sensors for chronic application towards individualized implants is here presented. To process thermal crosslinking polymers, the developed extrusion process enables, in combination with an infrared (IR)-Laser, accelerated curing directly after passing the outlet of the nozzle. As a result, no additional curing steps are necessary during the build-up. Furthermore, the minimal structure size can be achieved using the laser and, in combination with the extrusion parameters, provide structural resolutions desired. Active implant components fabricated using biocompatible materials for both conductive pathways and insulating cladding keep their biocompatible properties even after the additive manufacturing process. In addition, first characterization of the electric properties in terms of impedance towards application in neural tissues are shown. The printing toolkit developed enables processing of low-viscous, flexible polymeric thermal curing materials for fabrication of individualized neural implants.